2009
DOI: 10.1200/jco.2009.22.4386
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Second Primary Neoplasms of the Brain or Spinal Cord in Survivors of Childhood Cancer: Results From the British Childhood Cancer Survivor Study

Abstract: Our results indicate survival is poor after second primary glioma in this young adult population, although survival after second primary meningioma is good. Our study has clinical implications for the surveillance of childhood cancer survivors at risk of developing second primary brain tumors, in particular survivors of childhood acute lymphoblastic leukemia or childhood brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
2
23
1
1
Order By: Relevance
“…However, we observed a low number of SMNs that are known to appear late: meningiomas, with median latency of 23 years [36]; melanomas, with median latency of 14.6 years [16]; lung carcinomas, with median latency of 25.7 years [35]; or digestive carcinomas and  C. Berger et al NMSCs. Our findings show a high risk for bone and soft tissue secondary sarcomas, which resembles the results of other authors [14,16], but our elevated SIR (57.1) for thyroid carcinomas is higher than in other studies [9,12,14,37] and is probably related to the high number of patients treated with TBI in our cohort (14 …”
Section: Noted That Any Discrepancies Between Our Study and The Othermentioning
confidence: 65%
“…However, we observed a low number of SMNs that are known to appear late: meningiomas, with median latency of 23 years [36]; melanomas, with median latency of 14.6 years [16]; lung carcinomas, with median latency of 25.7 years [35]; or digestive carcinomas and  C. Berger et al NMSCs. Our findings show a high risk for bone and soft tissue secondary sarcomas, which resembles the results of other authors [14,16], but our elevated SIR (57.1) for thyroid carcinomas is higher than in other studies [9,12,14,37] and is probably related to the high number of patients treated with TBI in our cohort (14 …”
Section: Noted That Any Discrepancies Between Our Study and The Othermentioning
confidence: 65%
“…7, 13, 35, 36 Three of the studies were cohort studies and one was a single institution report. Two studies included the median age at first cancer diagnosis: 2·5 years and 4·3 years.…”
Section: Resultsmentioning
confidence: 99%
“…1113 A study utilizing the Surveillance, Epidemiology, and End Results (SEER) database reported a 10 year survival rate of 13·6% after subsequent CNS tumors after a primary diagnosis of pediatric solid tumors. 14 A report by Morris and co-workers reported that death due to subsequent neoplasms of the CNS was the second most common cause of death among five year survivors of CNS tumors, ranking only behind recurrence of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…2,11) Identical rates of grade II or III radiation-induced meningiomas and survival were reported compared to adult primary meningiomas. 28) In our institute, all radiation-induced meningiomas that have been presented to date have been WHO grade II. The atypical features of our cases might be related to the shorter follow-up periods of our surviving patients after treatment for childhood leukemia.…”
Section: Discussionmentioning
confidence: 99%